Germination of Juglans jamaicensis C. DC. subsp. jamaicensis, in nursery - José Luis Rodríguez Sosa; Calixto Aguilar Espinosa (Revista Cubana de Ciencias Forestales, 2013)
The species Juglans jamaicensis C. DC subsp jamaicensis, is in the red list of vascular flora Cuban critically endangered category since 1997. Granma province engrossed in reforestation needs to find ways to enable it to raise the percentage of survival of the positions in the field. The study was conducted in the nursery of the Teaching Unit of Forestry, University of Granma, with the aim of characterizing the germination of Juglans jamaicensis C. DC subsp. jamaicensis Nursery. Seeds were collected from isolated trees in the town of Pino del Agua, Sierra Maestra, grasping the ground under the tree and its surroundings. The seeds were subjected to pretreatment consisting of 24 hours immersion in water at room temperature, with changes every 12 hours and counting was performed for 90 days of germination, we also evaluated the response to transplantation. Germination began at 5 days and reached 57, 4%, showing erratic behavior. 7% of the seed used had not germinated after 90 days, while still viable, while 38% of the seed used had the embryo died. It achieved a 99, 3% success in the survival of seedlings.